دور الاعلام الرقمي الحكومي لدولة الإمارات في توظيف القوة الناعمه وإسهامه في تعزيز علاقاتها الدولية - عدنان حمد محمد الحمادي
The study aimed to know the reasons for the shortcomings and discrepancies in the role of government digital media towards employing initiatives, events, and developments as one of the types of Emirati soft power, by monitoring the extent to which government digital media adhere to professional standards and content and its uses of advanced applications in media coverage of the country externally while clarifying the role that it played towards Employing soft power and its repercussions in strengthening Emirati international relations, and demonstrating the extent of cooperation and partnerships between government digital media and the Emirates News Agency. The study sheds light on the role of the UAE Ministry of Foreign Affairs in forming partnerships with internal and external digital media in order to enhance Emirati soft power. It also sought to clarify the role that the incubator system for all government digital media should have, how to avoid shortcomings in government digital media in the future, and how to create a digital media that reaches the outside world and affects its people before their governments. The problem of the study was summed up by identifying the reasons for this discrepancy and shortcoming in the UAE government's digital media, despite the multiplicity of initiatives and significant events that represent the soft power of the UAE.The study relied on a qualitative approach through open questions and standardized interviews with a selection of the elite media, political and parliamentary leaders, and ministers familiar with the subject of the study. The study sample consisted of 15 participants who were chosen by the purposive, stratified method on the basis of their leadership qualities and their association with the subject of the study. Thus, the study reached the most important results, namely: Despite the availability of advanced applications for government digital media in the UAE, government digital media did not succeed in the transition with the soft power of the outside world despite the availability of all the requirements for success, due to the lack of a clear strategy and reference for the government digital media despite the multiplicity of the many initiatives, events, and activities of the UAE soft power, Based on these results, the following recommendations were developed: The most important of which is to identify the strengths of the unprecedented initiatives that embody soft power, focus on transferring it to the external recipient, expand the media message in cooperation and coordination with various digital media, and create media content that addresses the minds and hearts of the masses locally and abroad through The use of famous platforms and platforms internally and externally.